Universality of universal health coverage: A scoping review. - Aklilu Endalamaw; Charles F Gilks; Fentie Ambaw; Yibeltal Assefa (PLoS ONE)
Background The progress of Universal health coverage (UHC) is measured using tracer indicators of key interventions, which have been implemented in healthcare system. UHC is about population, comprehensive health services and financial coverage for equitable quality services and health outcome. There is dearth of evidence about the extent of the universality of UHC in terms of types of health services, its integrated definition (dimensions) and tracer indicators utilized in the measurement of UHC. Therefore, we mapped the existing literature to assess universality of UHC and summarize the challenges towards UHC. Methods The checklist Preferred Reporting Items for Systematic reviews and Meta-analysis extension for Scoping Reviews was used. A systematic search was carried out in the Web of Science and PubMed databases. Hand searches were also conducted to find articles from Google Scholar, the World Bank Library, the World Health Organization Library, the United Nations Digital Library Collections, and Google. Article search date was between 20 October 2021 and 12 November 2021 and the most recent update was done on 03 March 2022. Articles on UHC coverage, financial risk protection, quality of care, and inequity were included. The Population, Concept, and Context framework was used to determine the eligibility of research questions. A stepwise approach was used to identify and select relevant studies, conduct data charting, collation and summarization, as well as report results. Simple descriptive statistics and narrative synthesis were used to present the findings. Results Forty-seven papers were included in the final review. One-fourth of the articles (25.5%) were from the African region and 29.8% were from lower-middle-income countries. More than half of the articles (54.1%) followed a quantitative research approach. Of included articles, coverage was assessed by 53.2% of articles; financial risk protection by 27.7%, inequity by 25.5% and quality by 6.4% of the articles as the main research objectives or mentioned in result section. Most (42.5%) of articles investigated health promotion and 2.1% palliation and rehabilitation services. Policy and healthcare level and cross-cutting barriers of UHC were identified. Financing, leadership/governance, inequity, weak regulation and supervision mechanism, and poverty were most repeated policy level barriers. Poor quality health services and inadequate health workforce were the common barriers from health sector challenges. Lack of common understanding on UHC was frequently mentioned as a cross-cutting barrier. Conclusions The review showed that majority of the articles were from the African region. Methodologically, quantitative research design was more frequently used to investigate UHC. Palliation and rehabilitation health care services need attention in the monitoring and evaluation of UHC progress. It is also noteworthy to focus on quality and inequity of health services. The study implies that urgent action on the identified policy, health system and cross-cutting barriers is required to achieve UHC.